Strategies to Support Clinical Nursing Students Requiring Accommodations for Physical and/or Sensory Disability: A Scoping Review Protocol - Haghiri-Vijeh, Roya; Tsui, Joyce; Montague, Janet; Milly, Dima; Mussell, Jessica; Zakher, Bernadette; Dordunoo, Dzifa; Webber, Jennifer (Quality Advancement in Nursing Education / Avancées en formation infirmière)

(untitled) (Canadian Association of Schools of Nursing / Association canadienne des écoles de sciences infirmières, 2025)
Introduction: Post-secondary institutions are seeing increasing numbers of students requiring accommodation. In the clinical education of nursing students with physical and/or sensory disabilities, it is unclear what strategies are available to promote students’ success.Objective: The objective of this scoping review protocol is to identify the available evidence on strategies that have been implemented to support the clinical education of nursing students who require accommodation for a physical and/or sensory disability in the learning environment.Inclusion Criteria: This scoping review will consider studies that include nursing students with physical and/or sensory disabilities in any regulated nursing designation programs that use clinical placements as a component of nursing education. Peer-reviewed quantitative, qualitative, and mixed-methods studies; systematic reviews; unpublished dissertations; policy reports from schools of nursing; and text and opinion papers that focus on clinical education of nursing students will be included without limitations on language.Methods: Databases to be searched include Ovid MEDLINE, CINAHL (EBSCO), ERIC (EBSCO), APA PsycInfo (EBSCO), Web of Science, and Scopus. Unpublished studies and gray literature searches will be undertaken in ProQuest Dissertations & Theses and a limited number of relevant nursing websites. No limit on date or region will be applied. Records will be screened and extracted by two independent reviewers. Results will be presented as tables with an accompanying narrative summary.Discussion: As the number of students with physical and/or sensory disabilities in nursing education increases, nursing programs and educators must be aware of how to support these students to complete their education. The clinical learning environment poses unique challenges that need to be explored further. Findings will have implications for policy and programming in nursing education.